The rising costs of nutritious foods: The case of Ethiopia - Bachewe, Fantu Nisrane; Minten, Bart (International Food Policy Research Institute, 2019)
Costs of healthy diets are worryingly rising in a number of developed and emerging economies. However, less is known on these costs for developing countries. Using price data from a large number of markets in Ethiopia, we find that real prices of all nutritionally-rich food groups increased significantly (between 19 and 62 percent) over the period 2007 to 2016. This contrasts with (1) staple crops (grains, roots, and tubers), which did not show any price increase, and (2) oils, fats, and sugar, the prices of which decreased substantially. Using detailed nationwide datasets and relying on time series methods, we link these price increases to changes in local markets, demand and supply factors, transaction costs, and international trade. We find that prices of nutritionally-rich food groups – compared to cereals – are relatively less affected by international trade and exchange rate changes but more so by rapidly increasing local and city demand. This rising demand is likely due to recent income growth and rapid urbanization and the high-income elasticities for nutritious foods in Ethiopia. Moreover, we find that local production changes affected prices of nutritious items little, but national price rises were found to have been significantly linked with food price rises in commercial clusters in the country. Changes in transaction costs – fuel and transport costs – explained relatively little of the observed food price changes.